A violência obstétrica e suas manifestações no cotidiano dos serviços de saúde: uma revisão integrativa - Vieira, Letícia Becker (Universidade do Vale do Rio dos Sinos, 2016)
Violence against women is a public health problem, it has manifested itself in different health services as in maternity and obstetric centers. This violence, called obstetric comprises a series of health interventions without proof of effectiveness, disrespectful treatment and neglect in care by health professionals to women in the birth process. Objective: To identify and analyze the scientific production by obstetric violence. Method: This is an integrative review of literature developed in the databases of the Virtual Health Library (VHL) through the descriptors "violence" and "birth" with the following guiding question: What is being produced scientifically on the topic violence obstetric and how it manifests itself in everyday health services? The inclusion criteria were: original articles, review and electronically available in full reflection and free on the theme. Results: 08 articles were selected to converging objective of the work. Studies reveal the manifestation of obstetric violence in everyday health services through professional conduct permeated by relations of power and authority associated with lack of empathy and emotional distress in health professionals. Fact that generates in women mixed feelings and a negative and frustrating experience of the birth process. Final thoughts: it is therefore considered that the obstetric violence involves a violation of the reproductive rights of women during pregnancy, childbirth and postpartum.
Keywords: Enfermagem; Saúde da mulher; Violência contra as mulheres; Violência obstétrica; Serviços de saúde; Nursing; Women's health; Violence against women; Obstetric violence; Health services